HYBRID LATTICE BOLTZMANN METHOD FOR THE SIMULATION OF BLENDING PROCESS IN STATIC MIXERS - LATT, JONAS; KONTAXAKIS, DIMITRIOS; CHATAGNY, LAURENT; MUGGLI, FELIX; CHOPARD, BASTIEN (International journal of modern physics. C, Computational physics, physical computation, 2013)
A lattice Boltzmann method is proposed to simulate the blending of two fluids in static, laminar mixers. The method uses a mesh-based algorithm to solve for the fluid flow, and a meshless technique to trace the interface between the blended fluids. This hybrid approach is highly accurate, because the position of the interface can be traced beyond the resolution of the grid. The numerical diffusion is negligible in this model, and it is possible to reproduce mixing patterns that contain more than one hundred striations with high fidelity. The implementation of this method in the massively parallel library Palabos is presented, and simulation results are compared with experimental data to emphasize the accuracy of the results.